Cardiac arrest in Acute Coronary Syndrome: predictors and prognosis. (24th May 2021) - Santos, M; Santos, H; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: on behalf of the Investigators of " Portuguese Registry of ACS " Introduction: Cardiac arrest (CA) is a potential complication of acute coronary syndromes (ACS) and it is, therefore, important to access its impact on prognosis and identify patients with higher risk of CA in the setting of ACS. Objective: To evaluate predictors and prognosis of CA in the setting of ACS. Methods: Based on a multicenter retrospective study, data collected between 1/10/2010 and 4/09/2019. Patients (pts) without data on previous cardiovascular history or uncompleted clinical data were excluded. Pts were divided in 2 groups (G): GA – pts without CA; GB - pts with CA during hospitalization. Logistic regression and survival analysis was performed. Results: Between 25718 pts with ACS, CA occurred in 651 (2.5%). GB was younger (65 ± 15 vs 67 ± 14, p < 0.001), had higher rates of smoking (35.8% vs 26.4%, p < 0.001), and lower rates of hypertension (62.3% vs 70.9%, p < 0.001), diabetes (25.7% vs 31.7%, p < 0.001), dyslipidaemia (53.8% vs 61.7%, p < 0.001), previous ACS (17.2% vs 20.6%, p = 0.037) and coronary artery bypass grafting (CABG) (1.9% vs 5.1%, p < 0.001). Both groups were similar regarding previous heart failure (p = 0.450) and chronic kidney disease (p = 0.560). GB had shorter times from first symptoms to admission (158min vs 243min, p < 0.001). GA had higher rate of non-ST-elevation myocardial infarction (MI) (78.6% vs 41.4%, p < 0.001), whether GB had higher rates of ST-elevation myocardial infarction (STEMI) (46.7% vs 18.1%, p < 0.001), namely anterior (54.9% vs 46.9%, p < 0.001). GB had lower blood pressure (BP) (122 ± 33 vs 139 ± 28, p < 0.001), higher heart rate (HR) (83 ± 23 vs 77 ± 19, p < 0.001), presented more frequently in Killip-Kimball class (KKC) ≥2 (37.6% vs 14.6%, p < 0.001), in atrial fibrillation (AF) (13.9% vs 7.0%, p < 0.001) and with right bundle block (10.6% vs 5.3%, p < 0.001). GB had higher rates of common trunk culprit lesion (CL) (3.9% vs 1.6%, p < 0.001), anterior descending coronary CL (49% vs 37%, p < 0.001), 1 vessel lesion (53.4% vs 38.5%, p < 0.001), lower CABG rates (4.3% vs 6.3%, p = 0.042), more left ventricle dysfunction (57.7% vs 38.7%, p < 0.001) and needed more frequently mechanical ventilation (35.3% vs 1.1%, p < 0.001), non-invasive ventilation (6.8% vs 1.6%, p < 0.001) and provisory pacemaker (9.4% vs 1.3%, p < 0.001). Logistic regression confirmed that older age (p < 0.001, OR 1.89, CI 1.35-2.64), higher HR (p < 0.029, OR 1.33, CI 1.03-1.71), lower BP (P < 0.001, OR 2.67, CI 1.94-3.68), KKC ≥2 (p < 0.001, OR 2.35, CI 1.84-3.00), AF at admission (p < 0.001, OR 1.84, CI 1.34-2.51), STEMI (p < 0.001, OR 4.08, CI 3.66-6.77), lower left ventricle function (p = 0.009, OR 1.38, CI 1.08-1.75) were predictors of CA. Event-free survival was higher in GA than GB (92.8% vs 83.3%, OR 1.68, p = 0.008, CI 1.41-2.47). Conclusion: As expected, CA in the setting of ACS is associated with poorer prognosis. Several characteristics of the pts may help to predict the development of CA during hospitalization, allowing earlier identification and prompt treatment.